No bicycle, no bus, no job the making of workers' mobility in the Netherlands, 1920-1990. (Studies in History, Technology and Society Ser., 2022)
For working people, the expenses of going to their jobs, in terms of time and cost, are a crucial aspect of daily life. As economic conditions and mobility systems changed in the twentieth century, this aspect of workers' lives underwent significant transformations. Historians have only begun to unravel how power and social inequality informed the governance of everyday mobility. Amid the turmoil of twentieth century economic booms and busts, war and austerity, and processes of (car-centered) suburbanization, how did low-income, rural, and migrant workers get to work in the Netherlands? Governing Workers' Mobility explores the political choices underlying workers' daily commute. Using archival collections, it uncovers the shaping role of workers and employers, detailing their understanding and response to past mobility barriers. It discusses workers' discovery of bicycles, buses, mopeds, and cars; highlights company efforts to support and control employees' mobility; and shows that today's predicaments have a longer history.